Men's accounts of depression: reconstructing or resisting hegemonic masculinity? - Emslie, C; Ridge, D; Ziebland, S; Hunt, K (2006)
There is evidence that depressive symptoms in men are often undiagnosed and untreated. It has been suggested that men may find it difficult to seek help because culturally dominant (or hegemonic) forms of masculinity are characterised by emotional control and a lack of vulnerability, while depression is often associated with powerlessness and the uncontrolled expression of emotion. However, very little research exists which examines men's experiences of depression. We analysed 16 in-depth interviews with a wide range of men with depression in the UK Our analysis explored associations between depression and men's gender identities. We found that, as part of recovery from depression, it was important for men to reconstruct a valued sense of themselves and their own masculinity. The most common strategy was to incorporate values associated with hegemonic masculinity into narratives (being 'one of the boys', re-establishing control, and responsibility to others). While this strategy could aid recovery, there was also evidence that the pressures of conforming to the standards of hegemonic masculinity could contribute to suicidal behaviour. In contrast, a minority of men had found ways of being masculine which were outside hegemonic discourses. They emphasised their creativity, sensitivity and intelligence, explicitly reflected on different models of masculinity and redefined their 'difference' as a positive feature. Our research demonstrates that it is possible to locate men who can, and will, talk about depression and their feelings; thus generalisations about depressed men always being silent are misleading. While some men will have the resources to construct identities that resist culturally dominant definitions of masculinity, many others will find it more useful (and perhaps less threatening) to re-interpret potentially feminising experiences as 'masculine'. Health professionals need to be aware of the issues raised by men's narratives which emphasise control, strength and responsibility to others.